2021
DOI: 10.1038/s41598-021-92847-z
|View full text |Cite
|
Sign up to set email alerts
|

Paternal and maternal long-term psychological outcomes after uterine artery embolization for severe post-partum hemorrhage

Abstract: This study intend to compare the long-term psychological impact (depression, post-traumatic stress disorder) on both partners between patients that underwent uterine artery embolization (UAE) for post-partum hemorrhage (PPH) and uneventful deliveries. Women who experienced severe PPH treated by UAE in our institution between 2003 and 2013 were identified in our obstetrical database. These cases were matched to controls with uneventful deliveries. Matching criteria were maternal age, parity, ethnicity, year of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 26 publications
(35 reference statements)
2
21
0
Order By: Relevance
“…Furthermore, this study included all the antenatal classes that women attended, regardless of their speci c methods or settings (at the hospital or in private settings). Additionally, the low response rate (27.6%) is also an important limitation, although it is comparable to other questionnaire studies (Baud, Meyer, Vial, Hohlfeld, & Achtari, 2011; Bernasconi et al, 2021;Eggel et al, 2021), particularly to online surveys (Nulty, 2008;Lambelet et al, 2021). It is possible that women with traumatic childbirth experiences, particularly following emergency caesarean sections, did not participate in this study.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Furthermore, this study included all the antenatal classes that women attended, regardless of their speci c methods or settings (at the hospital or in private settings). Additionally, the low response rate (27.6%) is also an important limitation, although it is comparable to other questionnaire studies (Baud, Meyer, Vial, Hohlfeld, & Achtari, 2011; Bernasconi et al, 2021;Eggel et al, 2021), particularly to online surveys (Nulty, 2008;Lambelet et al, 2021). It is possible that women with traumatic childbirth experiences, particularly following emergency caesarean sections, did not participate in this study.…”
Section: Discussionsupporting
confidence: 55%
“…Childbirth experience is one of these risk factors, as well as the mode of childbirth, the fear of childbirth, mental health status during pregnancy, and social support. The childbirth experience is a self-assessment of what a woman remembers about her birth (Taheri, Takian, Taghizadeh, Jafari, & Sarafraz, 2018), sometimes even many years later (Bernasconi et al, 2021;Simkin, 1991). More than just satisfaction with pain or care, the childbirth experience attempts to "measure feelings of control, expectancy satisfaction, con dence, and participation in decision making" (Taheri et al, 2018, p. 3).…”
Section: Introductionmentioning
confidence: 99%
“…Seven studies explored the association between PPH and post-traumatic stress disorder (PTSD) at different time points ranging from 1 month to 8 years after birth, indicating a potential association between PPH and PTSD. (16, 37, 40, 44, 47, 53, 60) Five studies found a higher risk of PTSD among women who had a PPH and/or UAE or EPH compared with women who did not experience a PPH. (16, 37, 44, 53, 60) Four of these studies also reported adjusted odds (aOR), risk ratios (aRR) or aHR and these studies suggested a significant association between PPH and PTSD up to eight years after birth [aRR=4.45 (1.5 month); aRR=2.46 (6 months); aHR= 3.44 (within 12 months); aRR=1.90 (36 months); aOR=5.1 (8 years)].…”
Section: Resultsmentioning
confidence: 99%
“…(16, 37, 40, 44, 47, 53, 60) Five studies found a higher risk of PTSD among women who had a PPH and/or UAE or EPH compared with women who did not experience a PPH. (16, 37, 44, 53, 60) Four of these studies also reported adjusted odds (aOR), risk ratios (aRR) or aHR and these studies suggested a significant association between PPH and PTSD up to eight years after birth [aRR=4.45 (1.5 month); aRR=2.46 (6 months); aHR= 3.44 (within 12 months); aRR=1.90 (36 months); aOR=5.1 (8 years)]. (37, 44, 53, 60) The other two studies did not have comparison groups, but reported respectively 5% prevalence of PTSD among women who had a PPH at two months after birth (40) and 64% prevalence of PTSD among women who had an EPH at the median follow-up of 26.5 months.…”
Section: Resultsmentioning
confidence: 99%
“…10 Therefore, it is of great significance to be familiar with and master the factors of pain in patients undergoing UAE and properly foresee the implementation of intervention measures to improve the overall quality of patients during hospitalization and improve treatment satisfaction. UAE is widely adopted for patients with various gynecological and obstetric conditions, such as adenomyosis, 11 postpartum hemorrhage, 12 and CSP. 13 Patients were placed in a flat position and routinely disinfected and covered with aseptic hole towels.…”
Section: Introductionmentioning
confidence: 99%